Treatments and cancer: implications for radiologists - Granata, Vincenza; Fusco, Roberta; Setola, Sergio Venanzio; Borzacchiello, Assunta; Della Sala, Francesca; Rossi, Ivano; Ravo, Ludovica; Albano, Domenico; Vanzulli, Angelo; Petrillo, Antonella; Izzo, Francesco (Frontiers in Immunology, 2025)
This review highlights the critical role of radiologists in personalized cancer treatment, focusing on the evaluation of treatment outcomes using imaging tools like Computed Tomography (CT), Magnetic Resonance Imaging (MRI), and Ultrasound. Radiologists assess the effectiveness and complications of therapies such as chemotherapy, immunotherapy, and ablative treatments. Understanding treatment mechanisms and consistent imaging protocols are essential for accurate evaluation, especially in managing complex cases like liver cancer. Collaboration between radiologists and oncologists is key to optimizing patient outcomes through precise imaging assessments.